Keadilan Distribusi Waris dalam Kitab Alfiyyah Zubad pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Fairness of Inheritance Distribution in the Alfiyyah Zubad Book in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Jeanny Maharani Dewangkoro; Elsa Tamalia Ananda Agustri; Yuwan Novita Rahmadhani; Anindya Putri Hapsari (DIRASAH: Jurnal Kajian Islam, 2025)
This study aims to analyze the concept of justice in inheritance distribution as taught in the Alfiyyah Zubad Book and its implementation in the learning process at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. The background to this research stems from the phenomenon of inconsistencies in the understanding and application of Islamic inheritance law within the Islamic boarding school environment, despite using the same classical teaching sources. This study employed a qualitative approach with a case study method. Data were obtained through participant observation, in-depth interviews with educators and students, and document analysis of books, teaching notes, and syllabi. The results indicate that the Alfiyyah Zubad Book emphasizes proportional justice based on sharia provisions, where each heir receives a share according to their position. However, in practice, variations in interpretation between educators and students were found, particularly in the application of the concept of al-'awl and cases of incompletely divided assets. Rounding off the share and family deliberation are frequently used practical solutions, although they deviate slightly from the book's formula. The conclusion of this study confirms that Alfiyyah Zubad provides a strong theoretical foundation for inheritance justice, but its implementation in Islamic boarding schools requires pedagogical innovation and in-depth training for caregivers. Recommendations focus on the development of contextual modules and the integration of case-based learning methods to strengthen the understanding of inheritance justice among students.